PREDICTION OF HOT CARCASS YIELD IN BEEF CATTLE USING FUZZY EXPERT SYSTEM - Santos, M. P.; Cattelam, J.; Vaz, M. A. B.; Feltrin, P. F.; Klein, D. R.; Leal, W. S.; Oliveira, J. A.; Pacheco, P. S.; Vale, M. M. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The aim of this study was develop a carcass yield estimator in beef cattle. The carcass yield was estimated applying an expert fuzzy model with two input variables (age and zebu genotype) and one output variable (carcass yield). The variables predicted by the model were compared with a database created from information drawn from scientific articles, from the years 2000 to 2006, whose contemplate the same variables of study. The minor deviations between the values experimentally measured yields of carcass values predicted by fuzzy modeling were observed in animals from groups with genotype 100% or 0% zebu, which showed deviations of 0.34 and 1.02 %, respectively. The influence of age on hot carcass yield was low compared to the deviations, while the influence of the degree of zebu blood was higher. The use of fuzzy modeling for the prediction of hot carcass yield in beef cattle is reliable with low standard deviation when compared to the literature.